General strategy for the synthesis of natural and unnatural dialkylmaleic anhydrides - Haval, Kishan P.; N. P. Argade (Journal of Organic Chemistry, 2008)
Starting from alkylidenesuccinimides, a wide range of dialkylmaleic anhydrides have been synthesized via the generation of a carbanion on a succinimide unit and its condensation with various alkyl halides as the key reaction.

General approach to 2,4-dialkyl-3-carboxybutyrolactones: an efficient synthesis of (+/-)-striatisporolide A and (+/-)-lichesterinic acid - Patel, Ramesh M.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
Starting from 2-alkylidene-3-methylsuccinimides, simple and efficient synthesis of the natural products striatisporolide A. lichesterinic acid and lichesterylic acid have been demonstrated via an acid catalyzed hydrolysis, esterification, OsO(4)-dihydroxylation and dehydrative cyclization pathway.
Keywords: 2-Alkylidene-3-methylsuccinimides; dehydrative cyclizations; lichesterinic acid; OsO(4)-dihydroxylation; striatisporolide A; synthesis